Transcriptomes of arbuscular mycorrhizal fungi and litchi host interaction after tree girdling - Bo eShu (Frontiers in Microbiology, 2016)
Trunk girdling can increase carbohydrate content above the girdling site and is an important strategy for inhibiting new shoot growth to promote flowering in cultivated litchi (Litchi chinenis Sonn.). However, girdling inhibits carbohydrate transport to the root in nearly all of the fruit development periods and consequently decreases root absorption. The mechanism through which carbohydrates regulate root development in arbuscular mycorrhiza (AM) remains largely unknown. Carbohydrate content, AM colonization, and transcriptome in the roots were analyzed to elucidate the interaction between host litchi and AM fungi when carbohydrate content decreases. Girdling decreased glucose, fructose, sucrose, quebrachitol and starch contents in the litchi mycorrhizal roots, thereby reducing AM colonization. RNA-seq achieved approximately 60 million reads of each sample, with an average length of reads reaching 100 bp. Assembly of all the reads of the 30 samples produced 671,316 transcripts and 381,429 unigenes, with average lengths of 780 and 643 bp, respectively. Litchi (54,100 unigenes) and AM fungi unigenes (33,120 unigenes) were achieved through sequence annotation during decreased carbohydrate content. Analysis of differentially expressed genes (DEG) showed that flavonoids, alpha-linolenic acid, and linoleic acid are the main factors that regulate AM colonization in litchi. However, flavonoids may play a role in detecting the stage at which carbohydrate content decreases; alpha-linolenic acid or linoleic acid may affect AM formation under the adaptation process. Litchi trees stimulated the expression of defense-related genes and downregulated symbiosis signal-transduction genes to inhibit new AM colonization. Moreover, transcription factors of the AP2, ERF, Myb, WRKY, bHLH families, and lectin genes altered maintenance of litchi mycorrhizal roots in the post-symbiotic stage for carbohydrate starvation. Similar to those of the litchi host, the E3 ubiquitin ligase complex SCF subunit scon-3 and polyubiquitin of AM fungi were upregulated at the perceived stages. This occurrence suggested that ubiquitination plays an important role in perceiving carbohydrate decrease in AM fungi. The transcription of cytochrome b-245 and leucine-rich repeat was detected in the DEG database, implying that the transcripts were involved in AM fungal adaptation under carbohydrate starvation. The transcriptome data might suggest novel functions of unigenes in carbohydrate shortage of mycorrhizal roots.